SIARAN RADIO PENDIDIKAN: UPAYA PERLUASAN AKSES LAYANAN PENDIDIKAN DI WILAYAH PERBATASAN INDONESIA - innayah, innayah (Jurnal TEKNODIK, 2018)
The aim of this study is to (1) describe the government’s policy on access to education on the border areas, (2) describe the condition of radio station in the border areas, and (3) explain the educational broadcasting model in the border areas. The method used is a documentary study towards the condition of educational services, RRI as a Public Broadcasting Institution (LPP), and the Local Indonesian Broadcasting Commission (KPID) in the border areas. The results of the study are: (1) the government has widened the educational access in the border areas through among others the construction of school infrastructure and dormitories, and the assignment of teachers to teach in the border areas, (2) LPP RRI and KPID in border areas have been broadcasting via radio stations in 12 provinces, and (3) the model of educational broadcast used in the border areas is the form of partnership between BPMRPK Yogyakarta, Ministry of Education and Culture with the radio stations in the border areas such as Public Broadcasting Institution (LPP), Local Public Broadcasting Institution (LPPL), Private Broadcasting Institution (LPS) as well as the Community Radio (Rakom). Tujuan penulisan artikel ini adalah untuk: (1) mendeskripsikan kebijakan pemerintah di bidang perluasan akses terhadap layanan pendidikan di daerah perbatasan, (2) menggambarkan keberadaan atau kondisi stasiun radio di wilayah perbatasan, dan (3) menjelaskan model siaran pendidikan di wilayah perbatasan. Metode yang digunakan adalah studi dokumentasi terhadap kondisi layanan pendidikan di perbatasan, Radio Republik Indonesia (RRI) sebagai Lembaga Penyiaran Publik (LPP), dan Komisi Penyiaran Indonesia Daerah (KPID) di wilayah perbatasan. Hasil kajian/ telaah mengungkapkan bahwa (1) pemerintah telah melakukan perluasan akses layanan pendidikan di wilayah perbatasan yang antara lain berupa pembangunan sarana-prasarana sekolah, asrama, dan pengiriman tenaga pengajar, (2) LPP RRI, dan KPID telah menyelenggarakan siaran di wilayah perbatasan di 12 provinsi, dan (3) model siaran radio pendidikan di wilayah perbatasan dilakukan dalam bentuk kerjasama kemitraan antara Balai Pengembangan Media Radio Pendidikan dan Kebudayaan Yogyakarta (BPMRPKKemendikbud) dengan stasiun radio, baik Lembaga Penyiaran Publik (LPP), Lembaga Penyiaran Publik Lokal (LPPL), Lembaga Penyiaran Publik Swasta (LPS) maupun Radio Komunitas (Rakom).